População de plantas e nitrogênio para feijoeiro cultivado em sistema de plantio direto - Souza Costa, Roberto Saverio; Arf, Orivaldo [UNESP]; Orioli Junior, Valdeci [UNESP]; Buzetti, Salatier [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2009)
The availability of nitrogen interferes in the dry matter quantity produced by the common bean crop, carrying on earlier or later closure of row spacings. Thus, the objective this study was to evaluate the response of common bean in three plants population (200, 240 and 300,000 plants per ha) in winter, to the nitrogen application at sowing (10 or 20 kg ha(-1)) and nitrogen rates at sidedressing (0, 25, 50, 75 and 100 kg ha(-1)). The experimental design was a randomized block with four replicates in a factorial arrangement 3x2x5. According to the results obtained it was concluded that: a smaller plants population provided significant increase on productivity. Nitrogen rates at sowing (10 or 20 kg ha(-1)) did not alter the common bean productivity. The application of increasing nitrogen rates proposed significant increment of productivity and the fertilization with 100 kg ha(-1) at sidedressing increased in 20% the grain productivity compared with the control.

A disponibilidade de nitrogênio interfere na quantidade de matéria seca produzida pelo feijoeiro acarretando fechamento mais cedo ou mais tarde das entrelinhas. Assim, o objetivo foi avaliar a resposta do feijoeiro cultivado em três populações de plantas (200; 240 e 300 mil plantas por ha), no período “de inverno”, à aplicação de nitrogênio na semeadura (10 e 20 kg ha-1) e doses crescentes de nitrogênio em cobertura (zero, 25, 50, 75 e 100 kg ha-1). O delineamento experimental foi o de blocos ao acaso disposto em um esquema fatorial 3x2x5, com quatro repetições. Pelos resultados obtidos conclui-se que: populações menores proporcionaram aumento significativo de produtividade. Doses de nitrogênio na semeadura (10 ou 20 kg ha-1) não alteraram a produtividade do feijoeiro. O fornecimento de doses crescentes de nitrogênio em cobertura proporcionou aumento significativo da produtividade, sendo que a adubação com 100 kg ha-1 de N em cobertura aumentou, em média, 20% a produtividade em relação à testemunha.
Plants population and nitrogen for common bean in no-tillage system
Keywords: Phaseolus vulgaris L; Nitrogen; Row spacings; No-tillage system